Isolation & Identification of Salmonella spp. which contaminated Poultry slaughter houses.: Ghazi Mousa Al-Khatib , Sahar Hassan Al-Qutbey - Al-Khatib, Ghazi Mousa (The Iraqi Journal of Veterinary Medicine, 2005)
This study was aimed to investigate the extent of pollution in Poultry slaughterhouse with Salmonella spp and their effect on public health .(142) samplescollected from (8) poultry slaughter houses in Baghdad were examined . thesesamples included( live chicken cages ,live chicken transporting cars,slaughtering knives ,workers hands, transport belt , chiller , chick beforepackaging stage) .All samples were cultured on special media until the growthappeared then Biochemical tests were done for diagnosis of Salmonella spp.The results of this study shown the diagnosis of (14) isolates of Salmonella spp,all of them were motile except (3) isolates, These isolates were recovered fromthe following sites:1. (2) isolates from live chicken transporting cars.2. (1) isolate from live chicken cages.3. (3) isolates from workers hands.4. (1) isolate from transport belt.5. (1) isolate from slaughtering knives.6. (3) isolates from chiller.7. (2) isolates from stunning.8. (2) isolates from chickens beforepackaging.